Krisis Akhlak di Era Globalisasi Digital: Analisis Integratif Perspektif Akidah Islam dan Hak Asasi Manusia - Winda Islamitha Nurhamidah; Mahmud Arif (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
This study examines the moral crisis in the era of digital globalization from the perspectives of Islamic creed (aqidah), ethics (akhlaq), and human rights (HAM). Using a qualitative approach with a library research design, this study analyzes various relevant academic sources to understand the dynamics of moral transformation influenced by technological advancement and global values. The findings indicate that digital globalization has significantly contributed to the shift of moral values, characterized by increasing individualism, permissiveness, and the weakening of ethical awareness in social interactions. In the Islamic perspective, such a crisis is closely related to the weakening of aqidah as the fundamental basis of moral behavior. Furthermore, the study reveals that while human rights principles share common ground with Islamic values in promoting justice and human dignity, differences arise in interpreting the concept of freedom. Therefore, a proportional and contextual understanding is necessary to harmonize these perspectives. This study concludes that strengthening aqidah, revitalizing Islamic moral values, and reinterpreting human rights within an Islamic framework are essential strategies to address moral challenges in the digital age. The integration of these elements provides a comprehensive approach to developing ethical awareness in contemporary society.